Cultural values and practices: the pillars of heritage language maintenance endeavours within an immigrant multilingual Malayali community in the UK. Issue 6 (2nd July 2020) - Meddegama, Indu Vibha
ABSTRACT: The widespread marginalisation of heritage languages in public and political discourse coupled with the association of proficiency in host languages with personal and professional gain have led many diasporic communities to shy away from transmitting their heritage languages at home (Curdt-Christiansen 2016): a context considered to be optimal for minority language maintenance (Vaccarino 2011). This does not imply however that attempts-on the part of migrants-to keep alive their heritage languages, are non-existent. Demonstrating a harmonious convergence between their everyday language practices and the above-mentioned assumption that the home is a 'stronghold' for heritage language use (Pauwels 2016 p.90) are a Malayali community based in Yorkshire, England. Making this a possibility was their commitment towards maintaining certain cultural practices and values associated with the first-generation migrants' country of origin, India. Drawing on semi-structured interview responses, observational field notes and audio-recorded family conversations obtained from this community, what I thus propose in this paper is that these cultural values and practices form the pillars that support the Malayalis' attempts to preserve their heritage language Malayalam. Furthermore, my findings suggest the agents behind these endeavours to pan across three generations, in two countries: the UK and India.